Correlation and comparison of some trace elements and their related proteins in Type 2 Diabetes mellitus in Kalars city/ Kurdistan-Iraq. - Saed, Hero; Zeyan Abdullah Ali (Al-Qadisiyah Journal of Pure Science, 2022)
The serum levels of trace elements alterations have been linked with Type 2 Diabetes mellitus (T2 DM) and its complication. The Objectives of this study is to detect the correlation relation between serum Chromium, Magnesium (Mg), Zinc (Zn), Copper (Cu), and Iron (Fe) with Fasting Blood Sugar (FBS) in patients with type two diabetes mellitus, also to study the comparison of Ferroxidase, Transferrin, and Total iron binding capacity in patients with type two diabetes mellitus with control groups. A total of forty subjects were included in this study, they were divided in two groups (control and diabetic patients). Fasting blood samples were taken from all participants and analyzed for levels of Cr, Mg, Zn, Cu, and Fe. The concentration of serum trace elements of each sample was determined by using Inductively Coupled Plasma Optical Emission Spectroscopy. A negative correlation was found between Mg, Zn, and Fe level in Type-2 diabetics with FBS, whereas serum copper level shows significant positive correlation with FBS, and chromium shown no significant correlation with FBS. Ferroxidase, and Total binding capacity showed a significant increase, while a significant decrease was found in Transferrin of T2DM.